Frédérique Ildefonse, La naissance de la grammaire dans l’antiquité grecque, París, Vrin, 1997, 490 pp. (Minerva, 2019)
Review: Frédérique Ildefonse, La naissance de la grammaire dans l’antiquité grecque, París, Vrin, 1997, 490 pp.